2017
DOI: 10.1073/pnas.1709190114
|View full text |Cite|
|
Sign up to set email alerts
|

Holocene fluctuations in human population demonstrate repeated links to food production and climate

Abstract: SignificanceThe relationship between human population, food production, and climate change is a pressing concern in need of high-resolution, long-term perspectives. Archaeological radiocarbon dates have increasingly been used to reconstruct past population dynamics, and Britain and Ireland provide both radiocarbon sampling densities and species-level sample identifications that are globally unrivalled. We use this evidence to demonstrate multiple instances of human population downturn over the Holocene that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
203
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(209 citation statements)
references
References 130 publications
5
203
0
1
Order By: Relevance
“…The most recent study suggests that climate deterioration might have resulted in the diversification of food production in Holocene (Bevan et al . ). A rapid transformation of subsistence strategies in the Early Bronze Age also occurred in the upper Yellow River Valley of North‐West China (Ma et al .…”
Section: Discussionmentioning
confidence: 97%
“…The most recent study suggests that climate deterioration might have resulted in the diversification of food production in Holocene (Bevan et al . ). A rapid transformation of subsistence strategies in the Early Bronze Age also occurred in the upper Yellow River Valley of North‐West China (Ma et al .…”
Section: Discussionmentioning
confidence: 97%
“…Other unaccounted factors may have had a stronger effect on the vegetated landscape. An obvious candidate is the dramatic increase in population density that occurred over the last 3,000 years (Bevan et al, 2017), which likely led to strong changes in land use practices, consequently disturbing vegetation throughout the continent. Earlier population rises and collapses during the Neolithic and Bronze Age could have also influenced the vegetated landscape in significant ways, although on a smaller scale (Shennan et al, 2013;Lechterbeck et al, 2014;Woodbridge, R. M. Fyfe, et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In this paper we use a version of the "UCL-method" (Shennan et al, 2013;Timpson et al, 2014;Edinborough et al, 2017). Such simulationbased models based on real archaeological datasets have shown to be useful for identifying changes related to population fluctuation in archaeological contexts (Edinborough et al, 2017:1;Bevan et al, 2017; see also Timpson et al, 2015). The paper by Edinborough et al (2017) has also demonstrated the value of this simulation-based method for studying early and mid-Holocene coastal population.…”
Section: Radiocarbon Dates and Summed Radiocarbon Probability Distribmentioning
confidence: 99%